A study on the effectiveness of the application of information technology in the teaching and learning of the grade 10 English listenning skill at Hermann Gmeiner school - Vinh - Ton, Anh Dao (ĐHNN, 2017)
The role of listening has undergone substantial changes in recent years. From being a neglected skill now it seems to be a core course in many language programs because good listening skill is not only valuable for its own sake but also for other aspects o (...)